Representasi Altruisme Wartawan Perang Marie Colvin dalam Film A Private War - Nurfaraini Fitri; Nina Siti Salmaniah Siregar; Taufik Wal Hidayat (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
This research aims to determine the Representation Altruism of Marie Colvin a War Journalists in the movie A Private War by using the semiotic perspective of Roland Barthes's which oriented towards Denotation, Connotation and Myth. The representation in A Private War presents a strong message of altruism, because this movie is not only showed with the aim of entertaining, but also to show the value of altruism / goodness that can be applied to the general public.  The biographical film, A Private War was made as the symbols to show morality, tolerance, empathy and respect to others  as the citizens of a country whose rights are also protected by law. Researchers used a qualitative methodology with a critical paradigm approach and descriptive research. Data collection techniques used were observation, documentation and interviews. Primary data obtained directly from observations on the object of research, a movie by Matthew Heineman entitled A Private War. Meanwhile, secondary data were obtained from library research and interviews with the informants to support this research. From this research, were found nine altruism of Marie Colvin, both in scenes and text in the form of conversation sentences in the movie A Private War.